2017
DOI: 10.2217/pme-2016-0079
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine in Circadian Rhythm Sleep–Wake Disorders: Current State and Future Perspectives

Abstract: In circadian rhythm sleep-wake disorders precision medicine is less developed than in other medical disciplines mainly because homeostatic sleep and circadian timing have a very complex phenotype with multiple genetic regulation mechanisms. However, biomarkers, phenotyping and psychosocial characteristics are increasingly used. Devices for polysomnography, actigraphy and sleep-tracking applications in mobile phones and other consumer devices with eHealth technologies are increasingly used. Also sleep-related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Dietary protein (PRO) may also influence sleep by supplying the body with amino acid tryptophan (TRP), which is a potential sleep-promoting nutrient [11]. TRP is first converted to 5-hydroxytryptophan (5-HTP), then to serotonin, which is then metabolized to melatonin to signal night time and the onset of sleep [16] A cross-sectional (CS) study has reported that the intake of PRO is positively correlated with sleep duration, quality and pattern [17]. However, studies on the effect of macronutrient distribution with sleep quality is limited and available results are inconsistent [18].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary protein (PRO) may also influence sleep by supplying the body with amino acid tryptophan (TRP), which is a potential sleep-promoting nutrient [11]. TRP is first converted to 5-hydroxytryptophan (5-HTP), then to serotonin, which is then metabolized to melatonin to signal night time and the onset of sleep [16] A cross-sectional (CS) study has reported that the intake of PRO is positively correlated with sleep duration, quality and pattern [17]. However, studies on the effect of macronutrient distribution with sleep quality is limited and available results are inconsistent [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another important sleep-related compound produced from serotonin is the hormone melatonin. This hormone is produced in the pineal gland and plays an important role in regulating the body's circadian rhythm ( 25 , 26 ). It has been reported that melatonin production decreases with age, especially in middle-aged and older individuals with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, one of the major challenges in Sleep Medicine is to develop precise diagnostic approaches and tailored interventions leading to Precision Sleep Medicine. The need for biomarkers for diagnosis, monitoring, prognosis and the prediction of treatment effectiveness has been extensively recognized for the majority of sleep disorders and associated morbidities, including Obstructive Sleep Apnea [ 32 , 33 ], cognitive impairment [ 34 ], sleep loss [ 35 ], hypersomnia [ 36 ], behavior disorders [ 37 ], and circadian rhythm sleep-wake disorders [ 38 ]. Furthermore, the application of pharmacogenetic methods [ 39 ] and precision tools for personalized treatment selection [ 40 ] holds the promise for developing uniquely tailored approaches for managing sleep-disorder patients.…”
Section: Sleep Disorders and Associated Morbidities Need For Precision Medicinementioning
confidence: 99%